An Observational Analysis of Suicidal Deaths during COVID 19 Pandemic Lockdown at Lucknow, India - Richa Choudhury (Indian Journal of Forensic Medicine & Toxicology, 2020)
COVID 19 Pandemic has affected the global population. . In this paper we have tried to study the possiblecontributing factors to suicides along with the demographic data of people committing suicides. Aimof the study- to analyse the role and magnitude of severity of these factors contributing to suicides anddevising possible strategies to help the vulnerable groups to cope with such situations in future. Material&methods- We had conducted an observational analysis of suicidal deaths which occurred in Lucknowduring the Lockdown period in India. Observations- A total 59 suicides were reported in Lucknow duringthe lockdown period of 69 days. Majority of suicides were done by Hanging (93.2%), Economic factorsaccounted for 49.2%, domestic conflicts 23.7%, psychological and emotional factors (27.1%). Conclusionwe should try to develop strategies and appropriate and timely interventions to eliminate the contributingpredisposing factors to suicide.